Cytology and Yields Analysis of Onions (Allium cepa l.) under Compost Application in Coastal Saline Soil: Cytology and Yields Analysis of Onions - Sadia, Taslim; Dutta, Dibakar; Das, Subroto Kumar; Nasrin, Afroja; Afroz, Mahin; Hossain, Md Uzzal (Journal of the Asiatic Society of Bangladesh, Science, 2025)
Onion (Allium cepa L.) is a valuable crop in Bangladesh for its diversified usage and availability of enriched germplasms including local and exotic ones. However, the cultivation of onions in the coastal regions of Bangladesh has become a major challenge because of salinity and soil fertility. Therefore, a pot experiment of coastal saline soil amendment with compost was carried out with mostly cultivated varieties i.e. Taherpuri and King. The treatments T1 (2.5 t/ha) and T2 (5.0 t/ha) significantly improved the plant height for the Taherpuri variety and revealed an escalation to the no. of the leaflet, root length and bulb diameter for the King variety. Compost application on saline soil didn’t increase the mitotic index (MI%) for all the treatments for both of the experimented varieties but increased the mitotic inhibition index (MII%) for the treatments T3 (7.5 t/ha) and T4 (10.0 t/ha) treatment for the Taherpuri and King varieties respectively. The correlation coefficient between the treatment and different yields of onion was found better for the Taherpuri than the King variety. J. Asiat. Soc. Bangladesh, Sci. 50(1-2): 89-99, June-December 2024